(untitled) (Jurnal Teknologi Industri Pertanian, 2026)
MSME XYZ, an artisan bakery business, faces challenges in meeting the demand for flour, its primary raw material, due to supply uncertainty, which amounts to up to 5% of the total demand. This issue results in missed production targets and a risk of declining product quality credibility. To address this problem, this study designs a supplier selection and order allocation (SSAO) system using the analytical hierarchy process (AHP), simple additive weighting (SAW), and multi-objective linear programming (MOLP) methods. The purpose of this research is to reduce the percentage of unfulfilled flour fulfilment at UMKM XYZ through order allocation planning based on the results of supplier performance evaluation. AHP is employed to determine the weights of supplier evaluation criteria, SAW is used to rank suppliers based on these weights, and MOLP is applied to optimize order allocation across four objective functions: minimizing delivery delays, minimizing quantity shortages, minimizing rejected products, and minimizing unmet demand. The proposed system demonstrates significant improvements: reducing delivery delays from 8 to 2 days, decreasing quantity shortages to 1 kg, lowering the total number of rejected products from 25 kg to 11 kg, and reducing the unmet demand rate from 5% to 2%. The SSAO system proves effective in improving raw material procurement efficiency and supporting the continuity of MSME XYZ’s production processes within the agro-industry value chain. Keywords: analytical hierarchy process, multi-objective linear programming, order allocation, simple additive weighting, supplier